2022
DOI: 10.2147/ijwh.s350510
|View full text |Cite
|
Sign up to set email alerts
|

Association of Higher Educational Attainment on Antenatal Care Utilization Among Pregnant Women in East Africa Using Demographic and Health Surveys (DHS) from 2010 to 2018: A Multilevel Analysis

Abstract: The use of antenatal care (ANC) plays a major role in minimizing maternal and child mortality through effective and appropriate screening, preventive, or treatment intervention. Even though almost all pregnancy-related mortalities are largely preventable through adequate use of ANC, sub-Saharan Africa (SSA), particularly East African Countries, continues to share the largest share of global maternal, and newborn mortality. Therefore, this study assesses if educational attainment is associated with optimal ANC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
7
24
1
Order By: Relevance
“…Furthermore, according to the latest Rwanda Demographic and Health Survey (RDHS), less than half of all the women are able to utilise more than four ANC contacts, yet over 94% deliver under the care of a SBA [ 16 ]. This is further supported by a regional paper that shows Rwanda to have the lowest optimal ANC utilization proportion [ 11 ]. In order to ensure successful implementation of the latest WHO ANC guidelines that recommend at least eight contacts for every pregnant woman and progress towards reduction of the MMR to less than 70 per 100,000 live births, there is need to explore the different factors such as quality of ANC that might affect utilisation of ANC [ 4 , 8 , 17 ].…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Furthermore, according to the latest Rwanda Demographic and Health Survey (RDHS), less than half of all the women are able to utilise more than four ANC contacts, yet over 94% deliver under the care of a SBA [ 16 ]. This is further supported by a regional paper that shows Rwanda to have the lowest optimal ANC utilization proportion [ 11 ]. In order to ensure successful implementation of the latest WHO ANC guidelines that recommend at least eight contacts for every pregnant woman and progress towards reduction of the MMR to less than 70 per 100,000 live births, there is need to explore the different factors such as quality of ANC that might affect utilisation of ANC [ 4 , 8 , 17 ].…”
Section: Introductionmentioning
confidence: 57%
“…Tiruye et al showed that attending at least one ANC contact can decrease the risk of neonatal death by 42% [ 10 ]. However, SSA regions such as East Africa continue to share some of the poorest ANC utilization statistics and a significant share of global maternal and newborn mortality [ 10 , 11 ]. This may be related to the quality of ANC care that is provided, which has been criticized in several studies from SSA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of understanding was suggested to associate with women’s educational level and literacy rate. In fact, it has been shown that the increase in women’s educational level is a major motivator for increasing the likelihood of her ANC attendance [ 16 , 17 ]. This suggests that educated women are more likely to have adequate knowledge of prenatal care services and understand the importance of early booking for ANC as well as attending the recommended eight visits [ 18 ].…”
Section: Discussionmentioning
confidence: 99%